Nonlinear ultrasonic imaging in pulse-echo mode using Westervelt equation: a preliminary research. (7th October 2019) - Chen, Wuxuan; Wang, Peng; Zhang, Zhihong; Deng, Xudong; Zhang, Congyao; Ju, Shenggen
Abstract: Acoustic nonlinear parameter β, was of great interest in tissue characterization in recent years. Nonlinear imaging methods have been reported to provide improved spatial and contrast resolution. We introduce a nonlinear imaging method derived from nonlinear wave equation based on Gaussian-form solution assumption, which can be applied in pulse-echo mode on diagnostic ultrasound. Through making the use of two pulse transmission, only nonlinear effects are reserved and other effects like scattering, diffraction and linear attenuation can be eliminated. For validation of this method a set of simulation results are generated with a nonlinear simulator. Simulated images also indicate that our method clearly describes the spatial distribution of B/A in the medium.